Internalization of Islamic Moral Values in the Rehabilitation of Inmates in Narcotics Correctional Institutions - Nining Suniarti; Mohd Winario; Saru Reza; Wahyu Febri Ramadhan Sudirman (Journal of Community Service and Empowerment, 2026)
The problem of drug abuse not only impacts legal and health aspects but also causes moral and spiritual degradation. Drug inmates generally face problems of weak self-control, low religious awareness, and a value crisis that impacts daily behavior. Therefore, correctional guidance needs to be complemented by an approach focused on strengthening morals and spirituality. This community service activity was carried out at the Class II B Rumbai Narcotics Correctional Institution in Pekanbaru with the aim of internalizing Islamic moral values ​​in the inmate development process. The objective of this activity was to instill Islamic moral values, such as honesty, responsibility, patience, discipline, self-control, and repentance, in order to shape the inmates' moral and spiritual awareness. Through internalization of these values, it is hoped that positive changes in attitudes and behavior will be sustained throughout the rehabilitation period and upon their return to society. The implementation methods included religious lectures, interactive discussions, self-reflection (muhasabah), habituation of worship, and moral-spiritual mentoring. A participatory approach was used to ensure that the rehabilitation process was not one-way but rather fostered inmates' internal awareness. Targeted outcomes include increased understanding and practice of Islamic moral values, the development of Islamic moral development modules, and the establishment of ongoing collaboration between universities and correctional institutions to support the rehabilitation and social reintegration of inmates.